Conceptual Issues of Linkage in the Assessment of Organizational Performance - Ford, Jeffrey D.; Schellenberg, Deborah A. (Academy of Management Review, 1982)
Current perspectives on the assessment of organization performance assume that organizations exhibit a oneness of structure and that the linkages among characteristics of organizations are rational. This paper examines the validity of these assumptions and their implications for assessing organization performance.